A systematic scoping review on the evidence behind debriefing practices for the wellbeing/emotional outcomes of healthcare workers - Evans, Thomas Rhys; Burns, Calvin; Essex, Ryan; Finnerty, Gina; Hatton, Ella; Clements, Andrew James; Breau, Genevieve; Quinn, Francis; Elliott, Helen; Smith, Lorraine D.; Matthews, Barry; Jennings, Kath; et al. (Frontiers in Psychiatry, 2023)
Debriefings give healthcare workers voice through the opportunity to discuss unanticipated or difficult events and recommend changes. The typical goal of routine debriefings has been to improve clinical outcomes by learning through discussion and reflection of events and then transferring that learning into clinical practice. However, little research has investigated the effects of debriefings on the emotional experiences and well-being of healthcare workers. There is some evidence that debriefings are a multi-faceted and cost-effective intervention for minimising negative health outcomes, but their use is inconsistent and they are infrequently adopted with the specific intention of giving healthcare workers a voice. The purpose of this systematic scoping review is therefore to assess the scope of existing evidence on debriefing practices for the well-being and emotional outcomes of healthcare workers. Following screening, 184 papers were synthesised through keyword mapping and exploratory trend identification. The body of evidence reviewed were clustered geographically, but diverse on many other criteria of interest including the types of evidence produced, debriefing models and practices, and outcomes captured. The current review provides a clear map of our existing understanding and highlights the need for more systematic, collaborative and rigorous bodies of evidence to determine the potential of debriefing to support the emotional outcomes of those working within healthcare.